2023
DOI: 10.1186/s12934-023-02134-x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-assisted sortase A cleavage of SUMOylated metallothionein constructs leads to high-yield production of human MT3

Abstract: Background Mammalian metallothioneins (MTs) are small (6–7 kDa), intracellular, cysteine-rich, metal-binding proteins involved, inter alia, in the homeostasis of zinc and copper, detoxification of heavy metals, antioxidation against reactive oxygen species, and protection against DNA damage. The high cysteine content (~ 30%) in MTs makes them toxic to bacterial cells during protein production, resulting in low yield. To address this issue, we present for the first time a combinatorial approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The study showed that liver cancer patients with lower levels of NPM1 have a better prognosis [ 27 ]. MT3 protects the body from DNA damage, and H2AX is a biomarker of DNA damage [ 28 , 29 ]. As one of the major REDOX regulators, TXNRD1 is associated with tumor aggressiveness and poor prognosis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that liver cancer patients with lower levels of NPM1 have a better prognosis [ 27 ]. MT3 protects the body from DNA damage, and H2AX is a biomarker of DNA damage [ 28 , 29 ]. As one of the major REDOX regulators, TXNRD1 is associated with tumor aggressiveness and poor prognosis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complicated IB purification and the recombinant protein refolding are hurdles to large (industrial) scale production. In this study, a simple and rapid recombinant protein production and purification method based on a bacterial surface display system [ 7 ] with calcium-dependent self-cleavage strategy [ 8 , 9 ] was attuned with modification for production of soluble PEN-HuscFv34 super antibody.…”
Section: Introductionmentioning
confidence: 99%
“…The Lpp′-OmpA′ is a chimeric protein consisting of a signal sequence and the first 9 N -terminal amino acids of the E. coli membrane-anchored lipoprotein (Lpp) which is fused to a transmembrane domain (amino acid residues 46–159) of OmpA (OmpA′) [ 7 ]. This chimeric protein has been used extensively for surface display of recombinant proteins in Gram-negative bacteria [ 7 , 9 15 ]. Usually, one cell of wildtype E. coli (with intact OmpA gene) can express as many as 100,000 OmpA molecules on the surface [ 7 ].…”
Section: Introductionmentioning
confidence: 99%